2018
DOI: 10.11607/ijp.5567
|View full text |Cite
|
Sign up to set email alerts
|

Peri-implant Tissue Health and Bone Resorption in Patients with Immediately Loaded, Implant-Supported, Full-Arch Prostheses

Abstract: The results suggest that plaque accumulation is correlated with peri-implant mucositis; however, plaque accumulation alone does not appear to be associated with bone resorption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 0 publications
2
28
0
4
Order By: Relevance
“…The majority of the implants was not affected by PITI and showed normal peri-implant bone levels (mean BR = 1.240 ± 0.87 mm). This is in agreement with the previous findings of the authors, in which high levels of plaque amount were not related to peri-implant bone resorption [6].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The majority of the implants was not affected by PITI and showed normal peri-implant bone levels (mean BR = 1.240 ± 0.87 mm). This is in agreement with the previous findings of the authors, in which high levels of plaque amount were not related to peri-implant bone resorption [6].…”
Section: Discussionsupporting
confidence: 94%
“…However, according to recent literature, even if mucositis can be related to plaque accumulation, the amount of plaque is not directly correlated with peri-implantitis and plaque accumulation alone does not cause peri-implant bone resorption. A study conducted by Menini et al showed successful clinical outcomes in patients treated with full-arch immediately loaded rehabilitations, recording no augmented bone resorption despite the presence of high levels of plaque around implants [6]. In addition, even if a proper oral hygiene is important, it is not always easy to maintain over time, especially in the case of old patients treated with fixed implant-supported full-arch prosthesis.…”
Section: Introductionmentioning
confidence: 99%
“…87 However, a recent clinical study over a follow up time of 1 to 14 years, reported that plaque accumulation alone did not appear to be associated with bone resorption around oral implants, even if there was evidence of increased soft tissue inflammation. 88 Plaque may in reality form after bone resorption has occurred around oral implants for whatever reason, rather than being the cause of bone resorption.…”
Section: On Factors With Particular Relevance For Oral and Orthopedmentioning
confidence: 99%
“…Immediate loading full-arch rehabilitations supported by dental implants have been demonstrated to be a predictable and effective approach to treat completely edentulous or seriously compromised dental arches [ 1 2 3 4 5 6 ]. However, early and late failures of implant restorations have been reported in the literature.…”
Section: Introductionmentioning
confidence: 99%